'Le Printemps Démocratique': Amazigh Activism in the February 20 Movement in Southern Morocco. Issue 1 (2nd January 2016) - Rossi-Doria, Daniele
ABSTRACT: This article explores the participation of Amazigh activist groups in the so-called 'Moroccan Arab Spring', known as the February 20 Movement (F20M). It analyzes the activism of diverse Amazigh militants in both urban and rural areas and their relationship with other F20M militant groups. The article interrogates the Amazigh's dilemma of multi-scalar engagement and explores activism within and beyond the F20M that led to the formal recognition of Amazigh rights and culture in Morocco, particularly Tamazight as an official language.